2002
DOI: 10.1111/j.2042-7174.2002.tb00662.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical care for older people: recording and review of medication following admission to hospital

Abstract: Focal points The National Service Framework for Older People calls for regular medication review for all patients over the age of 75 Studies have shown that pharmacists take more accurate admission medication histories than do junior medical staff, but few studies have evaluated pharmacist‐mediated medication review An ethnographic study was used to develop structured protocols for medication review and history taking, which were evaluated by a pharmacist on two acute medical wards The study found that a struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Hospital pharmacists have a major role advising on the selection and indications for rational drug use. It has been found that pharmacists carrying out reviews of medication resulted in more appropriate prescribing and fewer adverse drug reactions (Tulip et al 2002). However, the Nursing and Midwifery Council (NMC) (2004) has identified that part of the nurse's role is to be aware of potential side effects of medication.…”
Section: Polypharmacy In Older Peoplementioning
confidence: 99%
“…Hospital pharmacists have a major role advising on the selection and indications for rational drug use. It has been found that pharmacists carrying out reviews of medication resulted in more appropriate prescribing and fewer adverse drug reactions (Tulip et al 2002). However, the Nursing and Midwifery Council (NMC) (2004) has identified that part of the nurse's role is to be aware of potential side effects of medication.…”
Section: Polypharmacy In Older Peoplementioning
confidence: 99%
“…43 Evidence suggests that hospital pharmacists have been effective in improving the accuracy of documentation related to drug history, and decreasing prescribing costs and risk to patients. Hospital pharmacists have been encouraged to participate in post-admission ward rounds to detect inappropriate prescribing and reduce prescribing costs and medication errors.…”
Section: Medication Review Of the Care Of Older People In Acute And Smentioning
confidence: 99%